Modulation of DAPK1 expression by its alternative splice variant DAPK1-215 in cancer - QingShui Wang; ShuYun Weng; WenTing Zhong; YouYu Lin; Yan Yu; YiMin Huang; LiLin Ge; XiuLi Zhang; FangQin Xue; Yehuda G. Assaraf; Yao Lin (Journal of Translational Medicine)
Abstract Background Death-Associated Protein Kinase 1 (DAPK1) family members are calcium/calmodulin-regulated serine/threonine kinases implicated in cell death, normal development, and human diseases. However, the regulation of DAPK1 expression in cancer remains unclear. Methods We examined the expression and functional impact of a DAPK1 splice variant, DAPK1-215, in multiple cancer cell lines. DAPK1 and DAPK1-215 expression levels were quantified by qRT-PCR and Western blotting. Cell migration, invasion, and proliferation assays were conducted in vitro, and a zebrafish model was employed to evaluate metastatic potential. RNA pull-down and CLIP-seq analyses were performed to identify potential RNA-binding proteins. Finally, clinical liver cancer specimens were analyzed to assess the prognostic relevance of DAPK1-215 and DAPK1 mRNA levels. Results DAPK1-215 downregulated DAPK1 expression in liver, kidney, and gastric cancer cells by reducing DAPK1 mRNA stability. DAPK1-215 promoted migratory and invasive capabilities in liver and kidney cancer cells, but inhibited these processes in gastric cancer cells, without affecting cell proliferation. Mechanistically, DEAD-Box Helicase 3 X-Linked (DDX3X) stabilized both DAPK1-215 and DAPK1 mRNAs, suggesting that DAPK1-215 may act by competing for DDX3X binding to modulate DAPK1 mRNA stability. Importantly, high levels of DAPK1-215 correlated inversely with DAPK1 mRNA in liver cancer specimens and predicted poor prognosis, whereas high DAPK1 expression predicted improved patient outcomes. Conclusions Our findings unveil DAPK1-215 as a molecular brake on DAPK1 expression, influencing cancer cell migration and invasion in a context-dependent manner. These results highlight the potential of DAPK1-215 as an important regulator of malignant progression and as a prognostic marker in liver cancer.